Effect of Quick Response (QR) Code Identification (ID) Card on the Students’ Attendance Monitoring at Jesus F. Magsaysay Technical Vocational High School - Pantilon, Lasheundra Nie B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This quasi-experimental study investigated the effectiveness of Quick Response (QR) Code identification cards in monitoring student attendance at Jesus F. Magsaysay Technical Vocational High School during the 2022–2023 academic year. A total of 200 participants, including students, teachers, and administrators, provided data through surveys and interviews. Findings revealed that the QR Code ID system significantly enhanced attendance monitoring, with 78% of respondents reporting improved accuracy and 85% describing the system as easy to use. Statistical analysis showed a significant increase in attendance rates (t(99)=10.07, p<.05), indicating that the technology positively influenced student attendance behavior. Additionally, 70% of participants observed better punctuality and consistency among students. Although minor technical issues and unclear usage guidelines were identified, these challenges did not outweigh the system’s overall benefits. The results affirm the effectiveness of QR Code technology in improving attendance tracking and promoting student responsibility. Broader adoption, coupled with ongoing system updates and user training, is recommended to further enhance performance and support the advancement of digital attendance management in educational institutions.